Pro-environmental behavior model creating circular economy in steel recycling market, empirical study in Thailand - Wareerath Akkalatham; Amirhossein Taghipour (Environmental Challenges, 2021)
The purpose of this study is to examine the variables that influence both the Circular Economy (CE) and pro-environmental behavior in steel recycling manufacturing companies in Thailand. To develop and examine a model using structural equation modeling (SEM), we used a set of CE indicators proposed in previous studies. The variables identified in this study were determined through responses from stakeholders in the steel manufacturing and scrap management industries. A questionnaire-based survey was used to analyze the study target's (foundries, castings, and steel recycling manufacturers) behavior. Respondents contended that they value long-term relationships with suppliers. Quality control has a sizable impact on lean manufacturing techniques. Recycling costs and environmental concerns both have an effect on how behavioral control is perceived. It is critical for society to be educated about the circular economy and its practices. Environmental commitment is the most critical factor in the circular economy's success. The findings indicate that the most significant influence on the Circular Economy is the social willingness to recycle (CE). The study investigates the relationship between social willingness to recycle (SWR) and lean manufacturing techniques (LMT) and the success of circular economy practices. Environmentally responsible behavioral practices both promote and contribute to high levels of productivity. The CE's promotion is critical in light of the current trend toward globalization. We propose that steel manufacturers must continue to innovate in technical or non-technical ways, most notably through the use of efficient equipment such as pre-shredders, shredders, and power plants that accelerate long-term mineral resource savings.
Keywords: Sustainable Supply Chain Management; Environmental Sustainability in Business; Sustainable Building Design and Assessment